Characterization of polycyclic aromatic hydrocarbons (PAHs) in small craft harbour (SCH) sediments in Nova Scotia, Canada. (December 2018) - Davis, Emily; Walker, Tony R.; Adams, Michelle; Willis, Rob
Abstract: Polycyclic aromatic hydrocarbons (PAHs) have been widely studied in sediments due to their ubiquity and persistence in aquatic environments and potential for impairment to biota. Small craft harbour (SCH) sediments in Nova Scotia (NS), Canada, have yet to be studied comprehensively. SCHs are essential to the fishing industry, which is important for the Canadian economy. This spatiotemporal characterization study evaluated thirty-one SCHs across NS between 2001 and 2017 by analyzing sediment reports (secondary data). Sediment PAH concentrations varied widely across all SCHs. Few SCHs exhibited sediment PAH concentrations likely to impair biota based on comparison to sediment quality guidelines. Sediments in the Gulf region of NS were least impacted by PAHs, while the Southwest region was most impacted. Distribution of individual PAHs in sediments follows global trends, with high molecular weight PAHs dominating samples. Graphical abstract: Highlights: Sediment ∑PAH16 concentrations were spatiotemporally characterized in 31 NS SCHs spanning 17 years. Sediment ∑PAH16 concentrations ranged between 0.037 and 336.770 mg/kg. Only two SCHs exhibited mean ∑PAH16 concentrations expected to impair biota (>NOAA ERM guideline). Sediment ∑PAH16 concentrations provide valuable information for SCH characterization. Six individual high molecular weight PAH compounds dominate NS SCH sediments.